The Analysis Of Coffee Shop’s Business Strategy Formulation (A Case Study at Coffee & Chill, Bandar Lampung) - Saputra, Ahmad Fadli; Noviaristanti, Siska (eProceedings of Management, 2023)
This study aims to analyze the company's internal and external factors, and formulate an alternative companystrategy according to the company's condition using the QSPM Matrix. This study uses a qualitative descriptivemethod with interview, documentation and observation data collection techniques, and strategy formulation usingIFE, EFE, IE Matrix, CPM and QSPM Matrix. The results of this study resulted in an IFE matrix score of 3.01and an EFE matrix score of 3.43, which resulted in the IE Coffee & Chill matrix being in cell I and the rightstrategy for Coffee and Chill based on the IE matrix was the grow and build strategy. In this study, Coffee & Chillis ranked 2 with a total weighted score of 3, while for Café Kiyo and Kopi 20 it has a total weighted score of 3.14and 2.91. Based on the formulation of alternative business development strategies, it can be seen that the prioritystrategies to be implemented by Coffee and Chill in competing with its competitors are (1) Moving the newbusiness location to a strategic city center with a TAS value of 2,807. It can be concluded that from a number ofknown strategies, Coffee and Chill in moving its business location is accompanied by maintaining the advantagesand business opportunities that previously existed in the old location, namely continuing to create coworkingspace facilities, maintaining a relaxed and comfortable cafe atmosphere, moving business locations to a strategiccity center and continue to prioritize customer-oriented services.Keywords-IFE, EFE, CPM, QSPM, coffee.